2010
DOI: 10.1007/dcr.0b013e3181c75274
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Tibial Nerve Stimulation for the Treatment of Urge Fecal Incontinence

Abstract: This preliminary study demonstrates that percutaneous tibial nerve stimulation is an effective and very well tolerated treatment for patients with urge fecal incontinence with particular improvement in reducing fecal urgency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 25 publications
4
54
0
3
Order By: Relevance
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, improvements in patient quality of life have been observed. 22,24,25,26,27 Consistently, PTNS also improved the FI score and quality-of-life values in our study. In addition, 15 (68%) patients experienced more than 50% reduction in the number of FI episodes.…”
Section: Discussionsupporting
confidence: 87%
“…Following this publication, various materials, such as autologous fat, collagen analogs, and silicon, have been used and demonstrated positive results. 30,31 Although this method has been used for 20 years to treat FI, the optimal agent, quantity of the agent, injection technique, injection area and number of injections have not been clearly defined. 32 In our study, thin, solid polyacrylonitrile cylinders, first used by Ratto et al, 32 were used as an implant material.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous tibial nerve stimulation is an alternative minimally invasive technique for neurostimulation, utilizing the posterior tibial nerve at the ankle, that had gained popularity for the treatment of fecal incontinence [19,20]. It has not been formally investigated as a treatment modality for LARS.…”
Section: Sacral Neuromodulationmentioning
confidence: 99%
“…41 Similar to sacral nerve stimulation, posterior tibial nerve stimulation has been used in patients with urinary incontinence. It involves an office-based procedure, which involves repeated electrical stimulation of the posterior tibial nerve by needle insertion.…”
Section: Review Articlementioning
confidence: 99%
“…One prospective study of 31 patients with urge fecal incontinence reported improvement in 21 patients (68%) during a median follow-up of 9 months. 41 Patients with severe fecal incontinence in whom all conservative and surgical treatments fail can undergo fecal diversion as a last resort. A diverting colostomy is reserved for patients with poor quality of life.…”
Section: Review Articlementioning
confidence: 99%